MINERAL STATUS IN SOIL, FODDER AND BLOOD SERUM OF DAIRY COWS IN MIZORAM - Kalyan Sarma; Rajat Buragohain; Girin Kalita (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Mineral status of dairy cows in relation to commonly fed tree fodders, and soil mineral status were studied in Mizoram. The soil Ca, P and Mg were found to be below critical levels; but Cu, Zn and Fe were optimum in all studied locations. Except Ca, other minerals were estimated to be optimum in the tree fodders. However, except Fe, other minerals were found to be deficient in the serum of dairy cattle. The study indicated that mineral supplementation is necessary for maintaining production status of dairy cows in Mizoram.